Osmium concentration and isotopic composition of North Pacific deep-sea sediments - Bradley K Esser; Karl K Turekian (PANGAEA, 1988)
Pelagic clay and Mn nodules from DOMES sites in the North Pacific and a varved glacial lake deposit from Connecticut were analysed for Os concentration and isotopic composition by isotope-dilution secondary ion mass spectrometry after treatment by NiS fusion or oxalic acid leaching. Bulk pelagic clay from DOMES site C has 187Os/186Os = 6.5 and Os = 0.14 ng/g. Oxalic acid leaches of this same sediment and of Mn nodules from DOMES sites A and C have more radiogenic 187Os/186Os ratios which average 8.3. Bulk glacial Lake Hitchcock sediment has 187Os/186Os = 12.5 and Os = 0.06 ng/g. The total Os flux to North Pacific pelagic clay is 7 to 10 ng Os/cm**2/10**6 y. Lake Hitchcock sediment provides an integrated value for the local crustal 187Os/186Os ratio. The oxalic acid leaches are assumed to attack hydrogenous phases selectively. A simple model in which the only sources of Os to the ocean are continental crust with the isotopic composition of Lake Hitchcock (187Os/186Os = 12.5) and extraterrestrial particles with 187Os/186Os = 1.1 results in a cosmic flux of osmium to the sediment of 4.9 ng Os/cm**2/10**6 y of which 20% is hydrogenous. A model in which the sources of Os to the ocean are continental crust with an 187Os/186Os ratio of 30 (from the model of Palmer and Turekian, 1986), oceanic mantle or crust with 187Os/186Os = 1.04 and extraterrestrial particles with 187Os/186Os = 1.1 results in a cosmic flux of Os to the sediment of 5.7 ng Os/cm**2/10**6 y of which none is hydrogenous. These extraterrestrial Os fluxes correspond to maximum C-1 chondrite accretion rates of between 4.9 exttimes 104 and 5.6 exttimes 104 tonnes/y.
Supplement to: Esser, BK; Turekian, KK (1988): Accretion rate of extraterrestrial particles determined from osmium isotope systematics of Pacific Pelagic clay and manganese nodules. Geochimica et Cosmochimica Acta, 52(6), 1383-1388, https://doi.org/10.1016/0016-7037(88)90209-8